Investigation of the head's dynamic response to boxing punch using computer simulation - Boroushak, N.; Khoshnoodi, H.; Rostami, M. (Montenegrin Journal of Sports Science and Medicine, 2021)
Head injuries are dangerous injuries that are common in combat sports. Nevertheless, the mechanisms of concussion in sport have are not precisely known. Thus, this study aimed to investigate the dynamic response of the head based on linear and rotational accelerations in boxing using computer simulation. The ADAMS software model was used to determine the linear and rotational acceleration of boxing`s straight punch. The peak linear acceleration, average linear acceleration, peak rotational acceleration, and average rotational acceleration resulted from the straight punch to head were obtained: 75 g, 20 g, 4036 rad/s², 1140 rad/s², respectively; the impact times were 30 ms and 3 ms, respectively. The comparison of acceleration tolerance thresholds of head injury and obtained results of this study showed the rotational acceleration only leads to head injury. Furthermore, it is biomechanically improbable that the head would be moved only translationally or rotationally as a result of a straight punch. Therefore, both rotational and linear accelerations should be observed together for future studies.